Accessibility analysis of the web portals of the educational institutions in Cuenca, Ecuador - Campoverde Molina, Milton (2020)
This article shows the accessibility analysis of the websites of the educative institutions of Cuenca - Ecuador. The purpose of the research is to evaluate the accessibility of the websites with the Web Content Accessibility Guidelines (WCAG) 2.0 with a level of compliance A and analyze their regulatory compliance. Experiences and results of web accessibility research were investigated from a review of different bibliographic sources. The results obtained from the accessibility of 191 Web pages analyzed using the online tools Examiner, TAW, Markup Validation Service and CSS Validation Service are presented. Among the results, it is observed that it is necessary to correct errors in all the analyzed Web portals of the educational institutions of Cuenca. In order to establish the compliance level, the icons certifying the accessibility of the sites by the World Wide Web Consortium (W3C) in HTML, CSS and their conformity levels A, AA and AAA are verified. With the data obtained from the evaluation of the automatic tools, it is corroborated the compliance level of the success criteria of the WCAG 2.0 with a conformity level A. It is concluded that it is necessary to correct errors in all the web portals analyzed of the educational institutions of Cuenca. For the average number of errors found, it is more feasible for educational institutions to redesign their web portals in order to comply with the WCAG 2.0. They can also improve the fulfillment of the WCAG 2.0, with a hard work of revising and correcting the source code of their web portals.